Premature ovarian failure - Runnebaum, Benno; Rabe, Thomas (Reproduktionsmedizin, 1999)
The prevalence of a premature ovarian failure (POF) is about 1 % of all fertile women. The etiology of the disease is heterogenic and in most cases unknown. Patients history and determination of serum FSH (continously above 40 IE/l) is important. Concomitant diseases such as autoimmune diseases or a galactosemia must be excluded. Fertility cannot be improved by suppression of serum FSH by means of GnRH-analogues or Danazol followed by a high dose stimulation with gonadotropins or a pretreatment with estrogens. The prognosis in view to a pregnancy is unfavourable and in the individual case not predictable. A long term hormone replacement therapy is absolutely required in view to the health of the women with POF. In patients treated with biphasic HRT regimen a spontanous pregnancy cannot be excluded.
Es besteht kein Link zum Volltext des Artikels
Gesehen am 01.12.2020